Reintroduce Thalidomide? (A) - Diermeier, Daniel; Hermitage, Jason; Thaker, Shail; Heinze, Justin (London : Kellogg School of Management, 2006)
The case charts the history of the drug thalidomide from its dark beginnings causing child birth defects to the discovery that the drug could be used in the treatment of leprosy, certain cancers and HIV/Aids. The student is invited to consider how the FDA responded and approved the use of thalidomide for the treatment of these diseases.
Originally published in Diermeier, D., Hermitage, J., Thaker, S., & Heinze, J. (2006). Reintroduce thalidomide? (A). 5-104-003(A). Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; United States. -- Food and Drug Administration; Immunopharmacology; Thalidomide